PROBLEMS AND PROSPECTS OF DEVELOPMENT OF STRATEGIC MANAGEMENT IN UKRAINE - SACHYNSKA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The essence of strategic management and different approaches to its definition are considered. Under strategic management, we understand the dynamic process, which is based on the potential of the enterprise, is oriented on obtaining long-term competitive advantages on the market at timely adjustment of the goals of functioning (according to changes in the external environment) by means of innovative direction, growth of volumes of business, enterprise restructuring or anti-crisis management. The characteristic features of strategic management of the enterprise are given, which are based on a certain combination of management theories concerning the enterprise activity: in particular, on system and situation analysis, target and innovative approaches to management, etc.; the enterprise is considered as an open social - economic and material-substance system.The main goal of modern strategic management is to create such a system of management of the enterprise, which would allow to form mission and strategic goals of the enterprise on the basis of analysis of internal and external potential. In addition, develop, justify and implement functional and corporate strategies in a way that ensures effective achievement of high social and economic results. At domestic enterprises, the introduction of a system of strategic management is connected with many problems, in particular, with the realization that both current and strategic tasks need to be solved simultaneously in order to achieve the desired result. The expediency of strategy formation and introduction of strategic management into the practice of domestic enterprises is shown: by means of the strategy, the system of values is displayed, the views of the top management of the enterprise, his vision of the future will help to coordinate personnel in the necessary direction; the analysis of the enterprise environment will determine the limitations imposed by it and the possible evolution of its environment; the formed strategy will be a coordination tool that will ensure the goals, and in case of contradictions, will help to reach compromises, to diagnose the enterprise activity, determining the reasons for deviations between: results and goals; the formed strategy will increase the company’s adaptive readiness to unforeseen changes.
Keywords: strategy; strategic management; peculiarities of strategic management